Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1117/12.911382
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between organ dose and patient size in tube current modulated adult thoracic CT scans

Abstract: Recently published AAPM Task Group 204 developed conversion coefficients that use scanner reported CTDI vol to estimate dose to the center of patient undergoing fixed tube current body exam. However, most performed CT exams use TCM to reduce dose to patients. Therefore, the purpose of this study was to investigate the correlation between organ dose and a variety of patient size metrics in adult chest CT scans that use tube current modulation (TCM). Monte Carlo simulations were performed for 32 voxelized models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Provided that α value can be determined for a given TCM scan, the relationship between h and α may be used to obtain the organ dose conversion factors appropriate for the TCM scheme used. Alternatively, it was postulated that approximation methods may be used to take advantage of the existing organ dose conversion factors for fixed-mA scans, h FIXED (Khatonabadi et al 2011(Khatonabadi et al , 2013aLi et al 2011a). The accuracy of three approximation methods was evaluated.…”
Section: Evaluation Of Approximation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Provided that α value can be determined for a given TCM scan, the relationship between h and α may be used to obtain the organ dose conversion factors appropriate for the TCM scheme used. Alternatively, it was postulated that approximation methods may be used to take advantage of the existing organ dose conversion factors for fixed-mA scans, h FIXED (Khatonabadi et al 2011(Khatonabadi et al , 2013aLi et al 2011a). The accuracy of three approximation methods was evaluated.…”
Section: Evaluation Of Approximation Methodsmentioning
confidence: 99%
“…The second method was motivated by recent research (Khatonabadi et al 2011(Khatonabadi et al , 2013a; Li et al 2011a), which suggested that organ dose associated with a TCM scan may be approximated as…”
Section: Evaluation Of Approximation Methodsmentioning
confidence: 99%